واقع استخدام طلبة الصف العاشر لمواقع التواصل الاجتماعي (الفيس بوك) وعلاقته ببعض المتغيرات"دراسة ميدانية في مدينة اللاذقية" - جديد لبنى; مصطو مريانا (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The research aims to the reality of 10 th grade students studying of the social networks sites (face book )in Lattakia and the differences between their average scors in it according to sex varubles and hours of browsing and the means they browse with The researcher depended the discriptical and the motivated uses ,analyse method a questionar is been built and distributed on a sample of(162)students and (151)has returned full and valid for statistical analysis and a response rate of (93,21%) percent. And with the using of appropriate statical methods the most important results was: the exest of staticully significant differences between males and females students in surfing (FB)in favor of males. As well as Significant differences between students in the number of surfing hours .it was clearly found that students surf (FB) almostly 2hours a day and apeared significant differences in the way they use to surf that student tend to use cell phone more than disktop or net cafe the motives of student to surf(FB)in wich intertaiment and fun and communication with friends is the most important motive for students to surf(FB). يهدف البحث إلى دراسة واقع استخدام طلبة الصف العاشر لمواقع التواصل الاجتماعي (الفيس بوك) في مدينة اللاذقية, ودراسة الفروق بين متوسط درجاتهم في واقع الاستخدام تبعاً لمتغيرات الجنس وعدد ساعات التصفح, والوسيلة التي يتم بها التصفح, ودوافع الاستخدام. اعتمد البحث المنهج الوصفي, وتمّ بناء استبانة وتوزيعها على عينة بلغت (162) طالباً وطالبة, وأعيد منها (151) استبانة كاملة وصالحة للتحليل الإحصائي, وبنسبة استجابة بلغت (93.21%). وباستخدام الأساليب الإحصائية المناسبة كان من أهم نتائج البحث: وجود فروق دالة إحصائياً بين متوسطات درجات الطلبة الذكور والإناث في تصفح (الفيس بوك) لصالح الذكور, كذلك ظهرت فروقاً دالة إحصائياً بين متوسط درجات الطلبة في عدد ساعات التصفح, حيث تبين أنّ الطلبة يتصفحون الفيس بوك بحدود ساعتين في اليوم, وظهرت فروقاً دالة إحصائياً في الوسيلة التي يتمّ فيها التصفح, حيث يميل الطلبة إلى استخدام الهاتف الجوال أكثر من استخدامهم للحاسوب المنزلي ومقهى الانترنت, كما ظهرت فروقاً دالة إحصائياً في دوافع الطلبة لتصفح الفيس بوك, حيث يشكل الترفيه والتسلية والتواصل مع الأصدقاء أهم دوافع تصفح الطلبة للفيس بوك.